Cross border co-operation in rural areas giving the example of Bihar region - Bujdosó, Zoltán; Dávid , Lóránt; Uakhitova, Gulmira (Applied Studies in Agribusiness and Commerce, 2013)
After the political changes in 1990-ies in Hungary and in East-Central Europe the process of forming cross-border regional cooperations reached a new period. The border regions of the different national states join to encourage co-operation. The most remarkably connected system in our region is the Carpathian Euroregion. This paper deals with one of the most successful initiatives started between Hungary and Romania. The most outstanding co-operation of the past few years exists between the settlements of the former Bihar County which territory today belongs to two countries. The aims of the paper are to research the development of the border region; to reveal the factors of the cooperation and to observe the possibilities for the development. To obtain the goals desktop research, cluster analysis and data analysis were used, as statistic methods. The results emphasize that the development and renewal of the cross-border co-operations were supported by historical factors and good practices adapted from Western Europe. Although economic backwardness or the administrative problems are against the cooperation, historical economic connections facilitate the common work in the Hungarian-Romanian border region.